2021
DOI: 10.1088/1742-6596/1911/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Student Result Prediction in Covid-19 Lockdown using Machine Learning Techniques

Abstract: Covid-19 virus has moved the world to a static state. This has confused the education field in conducting the end examinations. The school education has declared the results of a few classes as pass without conducting the end examinations. But, this may not be possible for all the education system, especially for final year college student results. For this reason, the prediction of result based on their previous performance is essential. Prediction can be effectively achieved by using machine learning algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Figure 7 presents a bar of the frequency of studies based on the sample size. It is observed that only twenty-six (26) studies used a dataset with more than or equal to 1000 instances to train the predictive models ([13], [16], [58], [65], [68], [69], [80], [89], [90], [99], [107], [112], [27], [119]- [121], [123], [127], [129], [45], [46], [50], [51], [53], [55], [56]). However, it is known that most Machine Learning algorithms require a massive amount of data to perform well and produce accurate prediction results.…”
Section: B Dataset Sample Population Size and Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 presents a bar of the frequency of studies based on the sample size. It is observed that only twenty-six (26) studies used a dataset with more than or equal to 1000 instances to train the predictive models ([13], [16], [58], [65], [68], [69], [80], [89], [90], [99], [107], [112], [27], [119]- [121], [123], [127], [129], [45], [46], [50], [51], [53], [55], [56]). However, it is known that most Machine Learning algorithms require a massive amount of data to perform well and produce accurate prediction results.…”
Section: B Dataset Sample Population Size and Collection Methodsmentioning
confidence: 99%
“…The second highest is IBM SPSS for statistical approaches with 13% ( [13], [66], [70], [82]- [84], [86], [95], [120], [136]). Other most-used tools include Microsoft Excel (17%) ([20], [52], [117], [123], [135], [71], [82]- [84], [86], [89], [112], [115]), RapidMiner Studio (9%) ( [13], [49], [70], [86], [91], [107], [131]), Jupyter Notebook (7%) ( [115], [123], [124], [127], [132]), Orange and R Studio (4%) ( [62], [87], [116], [125], [128], [133] respectively), and Tableau (3%) ( [77], [127]).…”
Section: Prediction Approaches Algorithms Learning Outcome Type and T...mentioning
confidence: 99%
“…The smart education model, which takes advantage of information technology such as big data analysis and artificial intelligence, has become a trend for new types of education. By analyzing students' interests, hobbies, habits and other behaviours, it has a significant impact on their personal development and academic performance [3]. The key to predicting student behaviour is an understanding of behavioural patterns in students' habits.…”
Section: Introductionmentioning
confidence: 99%